Isolasi dan Identifikasi Jatrophone dari Akar Jarak Merah (Jatropha gossyptfolia) serta Evaluasi Sifat Toksik dan Sitotoksiknya - SAHIDIN I; ARDIANSYAH ARDIANSYAH; MUHAMAD TAHER (Fakultas Farmasi Universitas Pancasila, 2010)
Isolation and identitication of secondary metabolites from root of Jatropha gossypyolia, and also its biological activity test toward microbes and tumor cells have been conducted, Isolation was carried out by using vacuum liqiud chromatography (VLC) method (adsorbent: silica gel, eluent: mixture of n-hexane, ethylacetate, chloroform, and methanol). The isolate molecular structure Was determined by spectroscopic technique i.e. FTIR, NMR-ID, 13C-DEPT, NMR-2D, comparing the data obtained with related data from literatures. Its biological activity was evaluated against bacteria (Acetobacter sp., Escherecia coli, Staphylococcus aureus, and Streptococcus sp.), fungi (Aspergillus nigcr, Pentcillium sp. [grey], Penicillium sp. [White] and Rhizopus sp.), and murine leukemia P-388 cells. The results showed that the isolate is a white needle crystal which is identified as jatrophone. Jatrophone is very active toward Acetobacter sp. (bacteria) and A. niger (fungi) with growth inhibition Zone of 3,6 cm and 4.4 cm, respectively. Meanwhile, jatrophone has low activity against murine leukemia P-388 cells with IC50, > 100 µg/mL.